Corrosion resistance analysis of the weld metal of low-alloy high-strength steel considering different alloy compositions - Song, Liang; Peng, Yun; Zhao, Haiyan; Cao, Yang; Fang, Qian (Frontiers in Materials, 2022)
In order to find the weld metal of low alloy high strength steel with the strongest corrosion resistance, the corrosion resistance of hsal weld metal was studied under the consideration of different alloy compositions. The corrosion resistance of hsal weld metal with different alloy compositions of 460 MPa, 690 MPa and 980 MPa was analyzed in atmospheric environment and simulated seawater environment respectively. The results of corrosion weight gain test, weight loss test and Kelvin probe test show that hsal weld metal with 980mpa alloy composition has the best corrosion resistance in atmospheric environment; Through seawater immersion test and electrochemical test, it can be found that hsal weld metal with 980 MPa alloy composition has good corrosion resistance in simulated seawater environment, hsal with 690 MPa alloy composition has medium corrosion resistance, and hsal with 460 MPa alloy composition has the lowest corrosion resistance. The corrosion resistance of the weld zone is the best and that of the heat affected zone is the worst, in order to provide some help for the research in related fields.